MEMBANGUN KEUNGGULAN BERSAING MELALUI INOVASI, MANAJEMEN PENGETAHUAN DAN ORIENTASI PASAR (Studi Pada Usaha Mikro Produk Makanan Khas Riau di Kota Pekanbaru) - Farhas, Rizqon Jamil; Samsir, Samsir; Restuti, Sri (Jurnal Tepak Manajemen Bisnis, 2016)
The study is conducted on micro industries typical food products of Riau in Pekanbaru Citylisted in Riau Food Association (ASPARI) as the organization that houses the business operatorstypical food products of Riau in Pekanbaru. Purpose of this study is to determine the effect ofknowledge management and market orientation towards innovation and competitive advantage, andalso examine the effect of innovation on competitive advantage in micro industries typical foodproducts of Riau in Pekanbaru.The study population consisted of 108 respondents as micro industries typical food products of Riau,which are micro industries as well as samples of this study. The sampling method used is a censusmethod. Variables used are knowledge management and market orient ation as an independentvariable, as well as innovation and competitive advantage as the dependent variable. The analysis toolis Lisrel 8.80.Statistical tests results indicate that knowledge management had a positive but insignificant effect onthe innovation and competitive advantage, while market orientation had a positive and significant effecton the innovation and positive but insignificant effect on the competitive advantage. The researchresults also indicate that innovation had a positive and significant effect on the competitive advantagemicro industries typical food products of Riau in Pekanbaru city..